Student and faculty attitudes toward campus carry after the implementation of SB11 - Nodeland, Brooke (Applied psychology in criminal justice, 2019)
With increased attention given to highly publicized incidents of school shootings, Texas is among a handful of states that considered the implementation of a concealed carry policy on their university campuses. Texas State Senate Bill 11 (SB11) made it legal for handgun license holders to carry concealed handguns on college and university campuses, however, the debate surrounding campus carry continues as most states have made no such provision. The university surveyed, like many other in the state, held educational and information sessions to inform students, faculty and staff of the guidelines of the campus carry policy. The current study explores students and faculty/staff attitudes toward campus carry at a midsize southern suburban university in Texas shortly after the implementation of SB11 considering their awareness of the change to the campus carry policy. Findings suggest that students and faculty/staff have similar concerns surrounding campus carry, and also that similar factors predict their support, or lack thereof, for the policy.